2016
DOI: 10.5137/1019-5149.jtn.15649-15.4
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical changes in disc pressure and facet strain after lumbar spinal arthroplasty with charité™ in the human cadaveric spine under physiologic compressive follower preload

Abstract: and yet resist large compressive loads. As far as the load path remains within the limited range of the estimated rotation centers of the lumbar segments, the load-carrying capacity of the lumbar spine increases under a compressive follower load (19).We previously published a biomechanical study on the range of motion (ROM) changes following lumbar spinal arthroplasty █ InTRODuCTIOn T he lumbar arthroplasty technique was developed to maintain the biomechanical features of a healthy disc, to decrease the rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…27 . In vitro cadaveric study and nite element analysis suggested that abnormal loading and aberrant kinematics of the facet joints after lumbar TDR contributed to the FJD [28][29][30][31] .…”
Section: Discussionmentioning
confidence: 99%
“…27 . In vitro cadaveric study and nite element analysis suggested that abnormal loading and aberrant kinematics of the facet joints after lumbar TDR contributed to the FJD [28][29][30][31] .…”
Section: Discussionmentioning
confidence: 99%